Calcium silicate / nanocellulose composite membrane for water treatment and preparation method thereof
Through the preparation method of calcium silicate/nanocellulose composite membrane, the problem of difficulty in removing organic pollutants in traditional water treatment technology is solved, and efficient and low-cost water treatment effect is achieved.
Patent Information
- Application Number
- CN202510195679.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-25
AI Technical Summary
Existing water treatment technology is difficult to efficiently remove organic pollutants such as organic dyes and bovine serum albumin in water bodies, and the synthesis conditions of traditional CSH are harsh, costly, and have poor adsorption effect.
A calcium silicate/nanocellulose composite membrane is used, and a surfactant and calcium source are added to the sodium silicate solution, and the acidification treatment is carried out after ultrasonic treatment, forming a composite membrane with a high specific surface area combined with CNF to form a network structure.
It has achieved efficient removal of organic dyes and bovine serum albumin from water, with higher adsorption performance and filtration effect, low cost and environmentally friendly.
Smart Images

Figure CN119869466A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment and specifically relates to a calcium silicate / nanocellulose composite membrane for water treatment and a preparation method thereof. Background Art
[0002] Treatment of pollutants in water is a common problem encountered in many fields, and the safety of water resources is related to all aspects of people's lives. Common water treatment methods include sedimentation filtration, adsorption, osmosis and distillation. Among them, the adsorption method requires a material with a porous structure as an adsorbent. CSH (calcium silicate hydrate) is a common inorganic silicate material with the advantages of strong adsorption, low price and wide source of raw materials.
[0003] Organic pollutants with good solubility, such as organic dyes and bovine serum albumin, are difficult to remove in water bodies. Ordinary physical filtration and chemical precipitation cannot achieve good results. How to efficiently remove organic pollutants in water bodies has become a research hotspot. CSH, as a silicate powder with physical adsorption characteristics, is very suitable as a water treatment material. At present, because of its porous structure and good biocompatibility, the research direction of CSH is mainly focused on drug loading, sustained release and adsorption of pollutants. Studies have shown that CSH prepared by surfactants as mesoporous templates can be used in many aspects, such as cement, medicine, papermaking and coatings, because of its high specific surface area and special porous structure; acidification treatment can generate a large number of silica particles on the surface of CSH, which react with water molecules in the solution to form silanol groups and form hydrogen bonds with CNF (nanocellulose). There are many related studies. For example, in the paper with DOI 10.1016 / j.colsurfa.2018.01.014, sodium dodecylbenzene sulfonate was used as a template to form spherical micelles. Ultrasound was used during the reaction to prepare a porous spherical shell CSH, which increased its application in the field of drug delivery. The patent document number CN119215848A describes a nanomaterial with a hydrated CSH solute and hexadecyltrimethylammonium bromide as a total solvent and a preparation method, which can be used in low CO2 environments such as air. 2 These studies all utilized the adsorption characteristics of CSH and studied methods to enhance its application effect.
[0004] However, the synthesis of CSH requires high-temperature calcination or hydrothermal reactors, which are harsh conditions and high preparation costs. In addition, the synthesized sheet-like stacked structure CSH has a low specific surface area and poor adsorption effect. The powdered finished product also makes it difficult to separate and reuse the adsorbent. Therefore, it is very important to develop a low-cost, high-adsorption membrane for water treatment. Summary of the invention
[0005] The purpose of the present invention is to solve the above problems existing in the prior art and to provide a calcium silicate / nanocellulose composite membrane for water treatment and a preparation method thereof.
[0006] A calcium silicate / nanocellulose composite membrane for water treatment comprises A-CSH and CNF, wherein the mass fraction of the A-CSH is 65% to 85%; and the A-CSH is acidified calcium silicate hydrate.
[0007] The preparation method of the calcium silicate / nanocellulose composite membrane for water treatment is achieved by the following steps:
[0008] 1. Adding a surfactant to the sodium silicate solution, stirring to dissolve, and then ultrasonically treating to obtain a homogeneous solution;
[0009] 2. Adding a calcium source to the above homogeneous solution under ultrasonic conditions and continuing the reaction for 2 to 3 hours, changing an ice bag every 30 minutes during the reaction to control the reaction temperature at 20 to 50° C. After the reaction is completed, separating and drying to obtain U-CSH (unacidified calcium silicate hydrate), which is then acidified to obtain A-CSH;
[0010] 3. Add the above A-CSH and 2 wt% CNF dispersion into deionized water and stir to mix, then perform vacuum filtration and washing to obtain a filter cake, and after drying, obtain a calcium silicate / nanocellulose composite membrane for water treatment, thus completing the preparation method;
[0011] The mass volume ratio of A-CSH, CNF dispersion and deionized water in step 3 is (32.5-42.5) mg: (0.375-0.875) g: 100 mL.
[0012] Furthermore, in step 1, the concentration of the sodium silicate solution is 0.01 mol / L; and the ultrasonic treatment time is 20 to 30 min.
[0013] Furthermore, the surfactant in step 1 is CTAB (hexadecyltrimethylammonium bromide), TTAB (tetradecyltrimethylammonium bromide), TW-80 (Tween-80), SDBS (sodium dodecylbenzene sulfonate) or SDS (sodium dodecyl sulfonate).
[0014] Furthermore, the volume mass ratio of the sodium silicate solution and the surfactant in step one is as follows: when the surfactant is CTAB, the volume mass ratio of the two is 1000ml:0.3g; when the surfactant is TTAB, the volume mass ratio of the two is 1000ml:1.3g; when the surfactant is TW-80, the volume mass ratio of the two is 1000ml:0.14g; when the surfactant is SDBS, the volume mass ratio of the two is 1000ml:4.18g; when the surfactant is SDS, the volume mass ratio of the two is 1000ml:23.4g.
[0015] Furthermore, the calcium source in step 2 is calcium hydroxide, calcium chloride, calcium carbonate or calcium acetate; the molar volume ratio of the calcium source to the homogeneous solution is 0.01 mol:1000 mL.
[0016] Furthermore, the separation and drying described in step 2: the flocculent white precipitate produced after the reaction is completed is separated by filtering through a sand core funnel, and then placed in an oven and dried at 45° C. for 24 hours.
[0017] Furthermore, the acidification treatment in step 2: U-CSH is mixed with distilled water to prepare a suspension with a solid content of 10-20%, and then 0.1 mol / L dilute hydrochloric acid is added to adjust the pH value to 4-5, and after acidification for 0.5-1h, magnetic stirring is performed at a speed of 300 rpm for 0.5h, and then washed alternately with deionized water and anhydrous ethanol three times, and finally placed in an oven at 40-50°C for 12-24h.
[0018] Furthermore, the vacuum filtration and washing in step three: vacuum filtration is performed using a sand core filter device with an inner diameter of 38 mm and a PVDF membrane with a diameter of 50 mm and a pore size of 0.45 μm, and then washing is performed alternately three times with distilled water and anhydrous ethanol.
[0019] Furthermore, the stirring in step 3 is carried out at a speed of 400 to 600 rpm for 0.5 to 1 hour; and the drying is carried out at a temperature of 60 to 80° C. and vacuum dried for 30 to 40 minutes.
[0020] The beneficial effects of the present invention are:
[0021] 1. The present invention provides a calcium silicate / nanocellulose composite membrane which is simple to prepare, low in cost, high in specific surface area and good in adsorption effect. The composite membrane consists of only two components, is environmentally friendly and non-toxic, and can be directly applied to water treatment.
[0022] 2. CSH has two morphologies: microporous block U-CSH and microsphere modified microporous block A-CSH. The present invention has found through research that compared with U-CSH, the silanol groups on the surface of A-CSH can form more hydrogen bonds with CNF, the structure is compact, and it has a higher specific surface area and porosity. Therefore, the present invention uses CNF as a skeleton and A-CSH as a filler to form a network structure to form a calcium silicate / nanocellulose composite membrane, which has better adsorption performance and better filtration effect, and can efficiently remove organic dyes and bovine serum albumin in water, wherein the organic dye removal rate can reach 90-95%, and the bovine serum albumin removal rate can reach 50-55%.
[0023] The present invention is suitable for the preparation of calcium silicate / nanocellulose composite membrane for water treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a scanning electron microscope image of U-CSH in Example 1;
[0025] Figure 2 is a scanning electron microscope image of A-CSH in Example 1;
[0026] Figure 3 is a scanning electron microscope image of U-CSH / CNF-75 in Comparative Example 1;
[0027] Figure 4 is a scanning electron micrograph of A-CSH / CNF-75 in Example 1;
[0028] Figure 5 is a scanning electron microscope image of U-CSH / CNF-75 in Comparative Example 1;
[0029] Figure 6 is a scanning electron micrograph of A-CSH / CNF-75 in Example 1;
[0030] Figure 7 is the water permeation rate of the calcium silicate / nanocellulose composite membrane for water treatment prepared in the examples and comparative examples;
[0031] Figure 8 is the malachite green (MG) removal rate of the calcium silicate / nanocellulose composite membrane for water treatment prepared in the examples and comparative examples;
[0032] Fig. 9 is the Congo red (GR) removal rate of the calcium silicate / nanocellulose composite membrane for water treatment prepared in the examples and comparative examples;
[0033] Fig.10 It is the bovine serum albumin (BSA) removal rate of the calcium silicate / nanocellulose composite membrane for water treatment prepared in the examples and comparative examples. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0035] Specific implementation method 1: In this implementation method, the calcium silicate / nanocellulose composite membrane for water treatment includes A-CSH and CNF; wherein the mass fraction of the A-CSH is 65% to 85%; and the A-CSH is acidified calcium silicate hydrate.
[0036] Specific embodiment 2: The preparation method of calcium silicate / nanocellulose composite membrane for water treatment in this embodiment is achieved by the following steps:
[0037] 1. Adding a surfactant to the sodium silicate solution, stirring to dissolve, and then ultrasonically treating to obtain a homogeneous solution;
[0038] 2. Adding a calcium source to the above homogeneous solution under ultrasonic conditions and continuing the reaction for 2 to 3 hours, changing an ice bag every 30 minutes during the reaction to control the reaction temperature at 20 to 50° C. After the reaction is completed, separating and drying to obtain U-CSH (unacidified calcium silicate hydrate), which is then acidified to obtain A-CSH;
[0039] 3. Add the above A-CSH and 2 wt% CNF dispersion into deionized water and stir to mix, then perform vacuum filtration and washing to obtain a filter cake, and after drying, obtain a calcium silicate / nanocellulose composite membrane for water treatment, thus completing the preparation method;
[0040] The mass volume ratio of A-CSH, CNF dispersion and deionized water in step 3 is (32.5-42.5) mg: (0.375-0.875) g: 100 mL.
[0041] Specific implementation method 3: This implementation method is different from specific implementation method 2 in that the concentration of the sodium silicate solution in step 1 is 0.01 mol / L, and the ultrasonic treatment time is 20 to 30 minutes. The other steps and parameters are the same as those in specific implementation method 2.
[0042] Specific embodiment 4: This embodiment is different from specific embodiment 2 in that the surfactant in step 1 is CTAB, TTAB, TW-80, SDBS or SDS. The other steps and parameters are the same as those in specific embodiment 2.
[0043] Specific implementation mode 5: This implementation mode is different from specific implementation mode 2 in that the volume mass ratio of the sodium silicate solution and the surfactant in step 1 is as follows: when the surfactant is CTAB, the volume mass ratio of the two is 1000ml:0.3g; when the surfactant is TTAB, the volume mass ratio of the two is 1000ml:1.3g; when the surfactant is TW-80, the volume mass ratio of the two is 1000ml:0.14g; when the surfactant is SDBS, the volume mass ratio of the two is 1000ml:4.18g; when the surfactant is SDS, the volume mass ratio of the two is 1000ml:23.4g. Other steps and parameters are the same as those in specific implementation mode 2.
[0044] Specific embodiment 6: This embodiment is different from specific embodiment 2 in that the calcium source in step 2 is calcium hydroxide, calcium chloride, calcium carbonate or calcium acetate; the molar volume ratio of the calcium source to the homogeneous solution is 0.01 mol:1 L. The other steps and parameters are the same as those in specific embodiment 2.
[0045] Specific embodiment 7: This embodiment differs from specific embodiment 2 in that, in step 2, the flocculent white precipitate produced after the reaction is separated by filtering through a sand core funnel, and then placed in an oven at 45° C. for 24 hours. The other steps and parameters are the same as those in specific embodiment 2.
[0046] Specific embodiment eight: This embodiment differs from specific embodiment two in that the acidification treatment in step two is as follows: U-CSH is mixed with distilled water to form a suspension with a solid content of 10-20%, and then 0.1 mol / L dilute hydrochloric acid is added to adjust the pH value to 4-5, and after acidification for 0.5-1h, magnetic stirring is performed at a speed of 300 rpm for 0.5h, and then the mixture is washed alternately with deionized water and anhydrous ethanol three times, and finally placed in an oven at 40-50°C for 12-24h. The other steps and parameters are the same as those in specific embodiment two.
[0047] Specific embodiment 9: This embodiment differs from specific embodiment 2 in that the vacuum filtration and washing in step 3 is: vacuum filtration is performed using a sand core filter device with an inner diameter of 38 mm and a PVDF membrane with a diameter of 50 mm and a pore size of 0.45 μm, and then distilled water and anhydrous ethanol are used to wash alternately three times. The other steps and parameters are the same as those in specific embodiment 2.
[0048] Specific embodiment 10: This embodiment differs from specific embodiment 2 in that the stirring in step 3 is carried out at a speed of 400-600 rpm for 0.5-1 h, and the drying is carried out at 60-80° C. under vacuum for 30-40 min. The other steps and parameters are the same as those in specific embodiment 2.
[0049] The beneficial effects of the present invention are verified by the following examples:
[0050] Embodiment 1:
[0051] The preparation method of calcium silicate / nanocellulose composite membrane for water treatment is achieved by the following steps:
[0052] 1. Adding a surfactant to the sodium silicate solution, stirring and dissolving, and then ultrasonically treating to obtain a homogeneous solution (i.e., sodium silicate-CTAB solution);
[0053] 2. Adding a calcium source to the above homogeneous solution under ultrasonic conditions and continuing the reaction for 2 hours, changing an ice bag every 30 minutes during the reaction to control the reaction temperature at 40°C, separating and drying after the reaction to obtain U-CSH (unacidified calcium silicate hydrate), and then acidifying to obtain A-CSH;
[0054] 3. Add the above A-CSH and 2 wt% CNF dispersion into deionized water and stir to mix, then perform vacuum filtration and washing to obtain a filter cake, and after drying, obtain a calcium silicate / nanocellulose composite membrane for water treatment, thus completing the preparation method;
[0055] The amount of A-CSH used in step 3 is 37.5 mg, the amount of CNF dispersion used is 0.625 g, and the amount of deionized water used is 100 mL.
[0056] The concentration of the sodium silicate solution in step 1 is 0.01 mol / L; and the ultrasonic treatment time is 20 min.
[0057] The surfactant in step 1 is CTAB.
[0058] In step 1, the amount of sodium silicate solution used is 1000 mL, which is prepared by dissolving 2.84 g of sodium silicate in deionized water, and then adding deionized water to make the volume 1000 mL to obtain a sodium silicate solution with a concentration of 0.01 mol / L; the amount of surfactant CTAB used is 0.3 g.
[0059] The calcium source in step 2 is calcium hydroxide, and the amount used is 0.74g.
[0060] Separation and drying in step 2: The flocculent white precipitate produced after the reaction is completed is separated by filtering through a sand core funnel, and then placed in an oven and dried at 45° C. for 24 hours.
[0061] The acidification treatment in step 2: U-CSH is mixed with distilled water to prepare a suspension with a solid content of 10%, and then 0.1 mol / L dilute hydrochloric acid is added to adjust the pH value to 4-5. After acidification for 0.5 h, magnetic stirring is performed at 300 rpm for 0.5 h, and then the mixture is washed alternately with deionized water and anhydrous ethanol three times, and finally dried in an oven at 45°C for 24 h.
[0062] The vacuum filtration and washing in step 3: vacuum filtration is performed using a sand core filter device with an inner diameter of 38 mm and a PVDF membrane with a diameter of 50 mm and a pore size of 0.45 μm, and then washed alternately three times with distilled water and anhydrous ethanol.
[0063] The stirring in step 3: stirring at a rotation speed of 500 rpm for 1 hour; the drying: vacuum drying at 75° C. for 30 minutes.
[0064] In this embodiment, the mass proportion of A-CSH is 75%, and the prepared calcium silicate / nanocellulose composite membrane for water treatment is recorded as A-CSH / CNF-75.
[0065] The morphology of A-CSH in this embodiment is a microsphere-modified microporous block with high specific surface area and small pores.
[0066] Embodiment 2:
[0067] The difference between this embodiment and embodiment 1 is that in step 3, the amount of A-CSH used is 32.5 mg, and the amount of CNF dispersion used is 0.875 g; the rest is the same as embodiment 1.
[0068] In this embodiment, the mass proportion of A-CSH is 65%, and the prepared calcium silicate / nanocellulose composite membrane for water treatment is recorded as A-CSH / CNF-65.
[0069] Embodiment 3:
[0070] The difference between this embodiment and embodiment 1 is that in step 3, the amount of A-CSH used is 35 mg, and the amount of CNF dispersion used is 0.75 g; the rest is the same as embodiment 1.
[0071] In this embodiment, the mass proportion of A-CSH is 70%, and the prepared calcium silicate / nanocellulose composite membrane for water treatment is recorded as A-CSH / CNF-70.
[0072] Embodiment 4:
[0073] The difference between this embodiment and embodiment 1 is that in step 3, the amount of A-CSH used is 40 mg, and the amount of CNF dispersion used is 0.5 g; the rest is the same as embodiment 1.
[0074] In this embodiment, the mass proportion of A-CSH is 80%, and the prepared calcium silicate / nanocellulose composite membrane for water treatment is recorded as A-CSH / CNF-80.
[0075] Embodiment 5:
[0076] The difference between this embodiment and embodiment 1 is that in step 3, the amount of A-CSH used is 42.5 mg, and the amount of CNF dispersion used is 0.375 g; the rest is the same as embodiment 1.
[0077] In this embodiment, the mass proportion of A-CSH is 85%, and the prepared calcium silicate / nanocellulose composite membrane for water treatment is recorded as A-CSH / CNF-85.
[0078] Comparative Example 1:
[0079] The difference between this comparative example and Example 1 is that the U-CSH (unacidified calcium silicate hydrate) obtained in step 2 is used directly without acidification; that is, the amount of U-CSH used in step 3 is 37.5 mg, and the amount of CNF dispersion used is 0.625 g; the rest is the same as Example 1.
[0080] In this comparative example, the mass proportion of U-CSH is 75%, and the prepared calcium silicate / nanocellulose composite membrane for water treatment is recorded as U-CSH / CNF-75.
[0081] The morphology of -CSH in this comparative example is a microporous block with low specific surface area and large pores.
[0082] Comparative Example 2:
[0083] The difference between this comparative example and comparative example 1 is that in step 3, the amount of U-CSH used is 32.5 mg, and the amount of CNF dispersion used is 0.875 g; the rest is the same as comparative example 1.
[0084] In this comparative example, the mass proportion of U-CSH is 65%, and the prepared calcium silicate / nanocellulose composite membrane for water treatment is recorded as U-CSH / CNF-65.
[0085] Comparative Example 3:
[0086] The difference between this comparative example and comparative example 1 is that in step 3, the amount of U-CSH used is 35 mg, and the amount of CNF dispersion used is 0.75 g; the rest is the same as comparative example 1.
[0087] In this comparative example, the mass proportion of U-CSH is 70%, and the prepared calcium silicate / nanocellulose composite membrane for water treatment is recorded as U-CSH / CNF-70.
[0088] Comparative Example 4:
[0089] The difference between this comparative example and comparative example 1 is that in step 3, the amount of U-CSH used is 40 mg, and the amount of CNF dispersion used is 0.5 g; the rest is the same as comparative example 1.
[0090] In this comparative example, the mass proportion of U-CSH is 80%, and the prepared calcium silicate / nanocellulose composite membrane for water treatment is recorded as U-CSH / CNF-80.
[0091] Comparative Example 5:
[0092] The difference between this comparative example and comparative example 1 is that in step 3, the amount of U-CSH used is 42.5 mg, and the amount of CNF dispersion used is 0.375 g; the rest is the same as comparative example 1.
[0093] In this comparative example, the mass proportion of U-CSH is 85%, and the prepared calcium silicate / nanocellulose composite membrane for water treatment is recorded as U-CSH / CNF-85.
[0094] Comparative Example 6:
[0095] The difference between this comparative example and Example 1 is that no surfactant is used in step 1 and no ultrasonic treatment is performed; the rest is the same as Example 1.
[0096] The CSH prepared in this comparative example is denoted as N-CSH.
[0097] result:
[0098] Scanning electron microscopy analysis of U-CSH and U-CSH / CNF-75 showed Figure 1 , Figure 3 and Figure 5 shown; from Figure 1 It can be seen from the figure that the prepared U-CSH is porous and blocky with large pores. Figure 3 and Figure 5 It can be seen that the surface of the prepared U-CSH / CNF-75 composite membrane is rough, and there are large pores between U-CSH and CNF.
[0099] A-CSH and A-CSH / CNF-75 were analyzed by scanning electron microscopy. Figure 2 , Figure 4 and Figure 6 As shown. Figure 2 It can be seen that the prepared A-CSH has large pores and many spherical particles are generated on the surface; Figure 4 and Figure 6 It can be seen that the surface of the prepared A-CSH / CNF-75 composite membrane is smooth, and the structure between A-CSH and CNF is tight.
[0100] The specific surface area and pore size analysis (BET) of N-CSH, U-CSH and A-CSH were performed. The results showed that the specific surface areas of N-CSH, U-CSH and A-CSH were 8.763 m 2 / g, 174.963m 2 / g and 640.972m 2 / g, indicating that the specific surface area of U-CSH prepared by ultrasonic treatment and surfactant is larger than that of N-CSH, while silica microspheres are generated on the surface of A-CSH after acidification, with a larger specific surface area than that of U-CSH, which greatly enhances the adsorption performance.
[0101] The water permeability, MG removal, GR removal and BSA removal rates of U-CSH / CNF-75, A-CSH / CNF-75, U-CSH / CNF-65, U-CSH / CNF-70, U-CSH / CNF-80 and U-CSH / CNF-85, as well as A-CSH / CNF-65, A-CSH / CNF-70, A-CSH / CNF-80 and A-CSH / CNF-85 were tested respectively (a micro sand core funnel was used for the test, the filtered liquid volume was 25 mL, and the average value of the filtration time for three tests was taken). The specific test steps are as follows: using the prepared calcium silicate / nanocellulose composite membrane for water treatment with different ratios as the filter membrane, pouring 25 ml of distilled water, MG, GR and BSA solution into a micro sand core funnel (filter diameter 20 mm, capacity: 25 ml) device, using a water circulation vacuum filtration device for filtration at a pressure of 0.09 MPa, using an ultraviolet spectrophotometer to measure the absorbance of the solution before and after filtration, and exploring its water permeability and filtration removal rate. Three sets of parallel samples were tested, and the results are as follows: Figure 7 to Figure 10 As shown. Figure 7 It can be seen that as the proportion of CSH in the composite membrane gradually decreases, the water permeability of the composite membrane gradually decreases, which means that the time required to filter the same volume of liquid gradually increases; when the proportion of CSH is the same, the water permeability of the acidified calcium silicate nanocellulose composite membrane is slightly lower than that of the unacidified calcium silicate nanocellulose composite membrane, and the time required to filter the same volume of liquid is also slightly longer, which is consistent with the results of the scanning electron microscope test. The acidified calcium silicate nanocellulose composite membrane is smoother than the unacidified calcium silicate nanocellulose composite membrane, and the surface pores are smaller, making it more difficult for liquid to pass through. Figure 8 , 9 It can be seen from Figures 1 and 10 that under the same CSH proportion, the pollutant removal rate of the acidified calcium silicate nanocellulose composite membrane is significantly higher than that of the unacidified calcium silicate nanocellulose composite membrane, indicating that the acidified calcium silicate nanocellulose composite membrane can more efficiently remove MG, GR and BSA in water. This shows that the calcium silicate nanocellulose composite membrane prepared by CSH with a high specific surface area has better filtration performance.
[0102] In summary, the present invention prepares a CSH with a high specific surface area through acidification treatment, which enhances the adsorption performance and also enhances the number of hydrogen bonds formed between it and CNF, thereby preparing a calcium silicate / nanocellulose composite membrane for water treatment that can efficiently filter organic pollutants in water.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. Calcium silicate / nanocellulose composite membrane for water treatment, characterized in that The invention comprises A-CSH and CNF; wherein the mass fraction of the A-CSH is 65% to 85%; and the A-CSH is acidified calcium silicate hydrate.
2. A method for preparing a calcium silicate / nanocellulose composite membrane for water treatment as claimed in claim 1, characterized in that It is implemented as follows:
1. Adding a surfactant to the sodium silicate solution, stirring to dissolve, and then ultrasonically treating to obtain a homogeneous solution; 2. Adding a calcium source to the above homogeneous solution under ultrasonic conditions and continuing the reaction for 2 to 3 hours, replacing an ice bag every 30 minutes during the reaction to control the reaction temperature at 20 to 50°C, separating and drying after the reaction to obtain U-CSH, and then acidifying to obtain A-CSH; 3. Add the above A-CSH and 2 wt% CNF dispersion into deionized water and stir to mix, then perform vacuum filtration and washing to obtain a filter cake, and after drying, obtain a calcium silicate / nanocellulose composite membrane for water treatment, thus completing the preparation method; The mass volume ratio of A-CSH, CNF dispersion and deionized water in step 3 is (32.5-42.5) mg: (0.375-0.875) g: 100 mL.
3. The method for preparing the calcium silicate / nanocellulose composite membrane for water treatment according to claim 2, characterized in that The concentration of the sodium silicate solution in step 1 is 0.01 mol / L; the ultrasonic treatment time is 20 to 30 min.
4. The method for preparing the calcium silicate / nanocellulose composite membrane for water treatment according to claim 2, characterized in that The surfactant in step 1 is CTAB, TTAB, TW-80, SDBS or SDS.
5. The method for preparing the calcium silicate / nanocellulose composite membrane for water treatment according to claim 2, characterized in that The volume mass ratio of the sodium silicate solution and the surfactant in step one is as follows: when the surfactant is CTAB, the volume mass ratio of the two is 1000ml:0.3g; when the surfactant is TTAB, the volume mass ratio of the two is 1000ml:1.3g; when the surfactant is TW-80, the volume mass ratio of the two is 1000ml:0.14g; when the surfactant is SDBS, the volume mass ratio of the two is 1000ml:4.18g; when the surfactant is SDS, the volume mass ratio of the two is 1000ml:23.4g.
6. The method for preparing the calcium silicate / nanocellulose composite membrane for water treatment according to claim 2, characterized in that The calcium source in step 2 is calcium hydroxide, calcium chloride, calcium carbonate or calcium acetate; the molar volume ratio of the calcium source to the homogeneous solution is 0.01 mol:1L.
7. The method for preparing the calcium silicate / nanocellulose composite membrane for water treatment according to claim 2, characterized in that Separation and drying in step 2: The flocculent white precipitate produced after the reaction is completed is separated by filtering through a sand core funnel, and then placed in an oven and dried at 45° C. for 24 hours.
8. The method for preparing the calcium silicate / nanocellulose composite membrane for water treatment according to claim 2, characterized in that The acidification treatment in step 2 is as follows: U-CSH is mixed with distilled water to form a suspension with a solid content of 10-20%, and then 0.1 mol / L dilute hydrochloric acid is added to adjust the pH value to 4-5. After acidification for 0.5-1h, magnetic stirring is performed at a speed of 300 rpm for 0.5h, and then the mixture is washed alternately with deionized water and anhydrous ethanol three times, and finally dried in an oven at 40-50°C for 12-24h.
9. The method for preparing the calcium silicate / nanocellulose composite membrane for water treatment according to claim 2, characterized in that The vacuum filtration and washing in step 3: vacuum filtration is performed using a sand core filter device with an inner diameter of 38 mm and a PVDF membrane with a diameter of 50 mm and a pore size of 0.45 μm, and then washed alternately three times with distilled water and anhydrous ethanol.
10. The method for preparing the calcium silicate / nanocellulose composite membrane for water treatment according to claim 2, characterized in that The stirring in step 3: stirring at a speed of 400-600 rpm for 0.5-1 h; the drying: vacuum drying at 60-80° C. for 30-40 min.
Citation Information
Patent Citations
Calcium silicate hydrate nano material as well as preparation method and application thereof
CN119215848A